2000
DOI: 10.1016/s0378-1097(00)00007-0
|View full text |Cite
|
Sign up to set email alerts
|

Sequence polymorphisms within the pMGA genes and pMGA antigenic variants in Mycoplasma gallisepticum

Abstract: Antigenic variants of Mycoplasma gallisepticum major surface lipoprotein, pMGA, are encoded by a large gene family. In this study sequence analyses of the PCR‐amplified pMGA genes showed two types of sequences similar to the pMGA1.2 gene in M. gallisepticum strains. They differed in the sequence encoding a proline‐rich region (PRR) at the N‐terminus of the pMGA protein. The type A genes had sequences similar to the published pMGA1.2 gene sequence of strain S6, whereas the type B genes lacked the second repetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Indeed, chickens infected with M. synoviae raised high levels of antibodies against MSPB, including antibodies which blocked binding of mAb 125 ( [5]; see also Section 3.2). Besides M. synoviae strain diversity in length of the predicted PRR, we observed diversity in the number of PNPT repeats in the N-terminal part of deduced pMGA sequences in M. gallisepticum strains [14]. Strain K1968 was the only M. synoviae strain capable of causing lesions in joints of chickens following eyedrop inoculation [3].…”
Section: Insertions or Deletions In The Vlha Gene Region Encoding Prrsmentioning
confidence: 83%
See 2 more Smart Citations
“…Indeed, chickens infected with M. synoviae raised high levels of antibodies against MSPB, including antibodies which blocked binding of mAb 125 ( [5]; see also Section 3.2). Besides M. synoviae strain diversity in length of the predicted PRR, we observed diversity in the number of PNPT repeats in the N-terminal part of deduced pMGA sequences in M. gallisepticum strains [14]. Strain K1968 was the only M. synoviae strain capable of causing lesions in joints of chickens following eyedrop inoculation [3].…”
Section: Insertions or Deletions In The Vlha Gene Region Encoding Prrsmentioning
confidence: 83%
“…In addition, rMSPB was used as a subunit MSPB antigen with a known number of residues and known amino acid sequence. Immunoblots were conducted with appropriate MSPB-speci¢c antibodies (mAbs or pAb RB), secondary antibodies labeled with horseradish peroxidase and diaminobenzidine tetrahydrochloride [10,14].…”
Section: Analysis Of the Mspb Protein Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…gallisepticum strains were grown in mycoplasma media with 10% horse serum. In most assays, type strain PG31 and strains S6, R and G11 were used as antigens (Benčina et al ., 1994;Miloševič-Berlič et al ., 2000). In the indirect immunoperoxidase assay (IIPA), M. gallinarum strain JA5 isolated from the chicken oviduct was also used .…”
Section: Methodsmentioning
confidence: 99%
“…Pourbakhsh et al (2010) suggested that these false negative results from culturing might be due to the deficiency of several substances (NAD, serum, CO 2 and certain other materials) in the medium and during transportation, over-chilling of the specimen and destruction of viable MS at room temperature. In addition, this strain contained a small amount of cytadhesins (MGC1 and MGC3) and no PvpA protein (Milosevic-Berlic et al, 2000). They isolated one MG strain (ULB 992) from the infra-orbital sinuses of peafowl and two MG strains (ULB 971 (trachea) and ULB 972) in vitro from pheasants.…”
Section: Diagnostic Procedures and Toolsmentioning
confidence: 99%